Bi and Branching Strict Nash Networks in Two-way Flow Models: a Generalized Sufficient Condition - Banchongsan Charoensook (Fondazione Eni Enrico Mattei (FEEM), 2018)
Bi and branching networks are two classes of minimal networks often found in the literatures of two-way flow Strict Nash networks. Why so? In this paper, we answer this question by establishing a generalized condition that holds together many models in the literature, and then show that this condition is sufficient to guarantee their common result: every non-empty component of minimal SNN is either a branching or Bi network. This paper, therefore, contributes to the literature by providing a generalization of several existing works in the literature of two-way flow Strict Nash networks.
Keywords: C72; D85; 330; Network Formation; Strict Nash Network; Two-way Flow Network; Branching Network